PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN SERTA DAMPAKNYA TERHADAP KEPUASAN KONSUMEN RUMAH MEBEL PEKANBARU - jordan Kevin; Nursanti Aida; Noviasari Henni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This reasearch aims to find out : 1) the effect of the marketing mix on purchasing decisions. 2) the effect of purchasing decisions on customer satisfaction. 3) the effect of the marketing mix on customer satisfaction through purchasing decisions. The population in this reasearch includes all Rumah Mebel consumers. Primary data were collected using a questionnaire as an instrument to prove the results of the study, to test the hypothesis in this study was to use path analysis and using SPSS program. The sampling technique used a purposive sampling method with the criteria that respondent had shopping furniture at the Rumah Mebel and live in the city of Pekanbaru with a total sample of 115 respondents. The results showed that: 1) Marketing Mix has a positive and significant effect on purchasing decisions for furniture products at Rumah Mebel. 2) Purchasing decisions have a positive and significant effect on consumer satisfaction who buys furniture products at Rumah Mebel. 3) Marketing Mix has a positive and significant effect on customer satisfaction through purchasing decisions.Keywords: Marketing Mix, Purchasing Decision, Customer Satisfaction